2021
DOI: 10.1111/mec.15815
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater zooplankton microbiome composition is highly flexible and strongly influenced by the environment

Abstract: The association with microbes in plants and animals is known to be beneficial for host's survival and fitness, but the generality of the effect of the microbiome is still debated. For some animals, similarities in microbiome composition reflect taxonomic relatedness of the hosts, a pattern termed phylosymbiosis. The mechanisms behind the pattern could be due to co‐evolution and/or to correlated ecological constraints. General conclusions are hampered by the fact that available knowledge is highly dominated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 84 publications
(134 reference statements)
6
60
1
Order By: Relevance
“…In conclusion, our results are in contrast with prior zooplankton microbiome research indicating that microbe composition is predicted by the environment [8]. Moreover, the two species examined here were reared in the same environmental conditions, suggesting hosts may be able to maintain the microbial communities associated with their natural environment.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In conclusion, our results are in contrast with prior zooplankton microbiome research indicating that microbe composition is predicted by the environment [8]. Moreover, the two species examined here were reared in the same environmental conditions, suggesting hosts may be able to maintain the microbial communities associated with their natural environment.…”
Section: Discussioncontrasting
confidence: 99%
“…While most host-associated microbiomes are strongly associated with host phylogeny [21][22][23][24][25], the differences between these two species are striking, as these two distantly related species have been cultured in similar in-laboratory rearing conditions for years. While phylosymbiosis, the hypothesis that host-associated microbial communities of closely related host species are more similar to each other than to less related host species [26], has been observed in other invertebrate species, this pattern is not frequently observed in zooplankton species, as much of their microbiome is acquired from the environment [8,27]. The differences in community composition between D. dentifera and D. magna in this study, as well as the differences among other zooplankton species as demonstrated by Eckert et al [8], provide some evidence that zooplankton microbiomes are relatively distinct.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The bacterial community associated with the same zooplankton population (Moina or Calanoids) also exhibits differences which may result from different characteristics of their ambient environment (Figure 2 and Table S1). Previous studies have demonstrated that the assembly of the ZA shows a strong environmental effect, suggesting that environmental variables also play an important role in shaping the zooplankton microbiome [40].…”
Section: Community Structures Of Zooplankton−associated Bacteria In Freshwater Lakesmentioning
confidence: 99%